Influence Explicit Instruction Learning Model Strategy Against Results Study Participant Educate on Subjects Accountancy Class XI PIS SMA Negeri 4 Pematangsiantar Year Teachings 2023/2024 - Nainggolan, Hanna Lestari; Sinaga, Anggun Tiur Ida; Sihombing, Sotarduga (Journal of Educational Analytics, 2024)
This research aims to prove the influence of strategy Explicit instruction learning model on student learning outcomes in the accounting subject class XI PIS SMA Negeri 4 Pematangsiantar. This type of research is quantitative research . The population in this study was all students in class XI PIS SMA Negeri 4 Pematangsiantar with a total of 104 students. The sample in this study consisted of 2 classes, namely class XI PIS-1 and class PIS-3 with a total of 68 students. Study done on March 26 – April 22 2024. Based on the results of descriptive analysis, it shows that the average accounting learning outcome in working paper material in classes that do not use the explicit instruction learning model strategy is 75.30. Meanwhile, the average learning outcome of students in classes that use the explicit instruction learning model strategy is 80. The results of inferential statistics using Ms.Excel 2010 obtained Sig (2 Tailed) < ɑ or (0.037 < 0.05) and the calculated t value was obtained > t table (2.131 > 1.996). So, based on the testing criteria, it can be said that Ha is accepted, namely that there is a significant influence of the explicit instruction learning model strategy on student learning outcomes in accounting subjects, working paper material for class XI PIS SMA Negeri 4 Pematangsiantar for the 2023/2024 academic year